Book and Literary-Life Imaginaries: A Historical, Sociological and Socio-Critical Project - Glinoer, Anthony (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2016)
What can works of fiction about the literary life teach us about books, publishing, reading, and about the people who animate the communications circuit? As representations of the writer’s own milieu, novels that portray the literary life possess a particular reflexive knowledge about the universe of the book. It is to this astonishingly vast corpus from the nineteenth to the twenty-first century that the GREMLIN (Groupe de recherche sur les médiations littéraires et les institutions) has dedicated the core of its work. The publication of essay collections and special journal issues (Fictions du champ littéraire et Bohème sans frontière in 2010, “Le livre dans le livre” in 2011, Imaginaires de la vie littéraire in 2012, Romans à clés in 2014) has joined the online publication of bibliographies of French and Québécois novels about the literary life and of a vast database containing detailed records of more than 80 novels (see legremlin.org). Its intense collecting of raw material and analytical articles (about a hundred) has allowed the GREMLIN to map the territory of fictional literary life in France. This paper will endeavour to sketch some of the perimeters (the transmission of the book object, the mise en abyme of the creative process in the fiction itself, and forms of sociability such as salons as sites of encounter among principal fictive actors in the literary life). By way of example, I will examine at length the configuration of the publisher in the French novel. Once almost invisible in French novels of the literary life, characters of publishers later abound. Beginning with the novel that fashioned the lasting fictional image of the publisher, Balzac’s Illusion perdues (1839), I move into the contemporary moment to study (in the case of Échenoz, Pennac, Robbe-Grillet, Christine Angot, etc.) the representation of the publisher – his/her physical traits, places of sociability, social function, and speech. I will show that, contrary to what was usual even into the 1970s, the discourse of the publisher is now often elevated to the level of that of the fictive writer to express resistance to the commercialization of literary production.